The monetary transmission mechanism in the euro area: A VAR-analysis for Austria and Germany - Bernhard Bartels (Kiel Institute for the World Economy (IfW), 2009)
With the transition to the European Monetary Union (EMU), the instrument of monetary policy for individual member countries has been abolished. This step has led to serious challenges for the different states to stabilize their economies to various economic shocks. Different labor market rigidities lead to different responses to monetary impulses in the countries. This paper deals with this problem by setting up a VAR-analysis to investigate the different shocks on Germany and Austria. The results show that Germany experiences less fluctuation in growth and unemployment than Austria which can be assigned to higher labor market rigidities.
Keywords: D21; F14; L22; 330; Monetary transmission mechanism; vector autoregression; Transmissionsmechanismus; VAR-Modell; Arbeitsmarktflexibilisierung; Deutschland